ChemInform Abstract: Acid‐Catalyzed Synthesis of α‐Trifluoromethylthiolated Carbonyl Compounds. Issue 48 (December 2015) - Alazet, Sebastien; Ismalaj, Ermal; Glenadel, Quentin; Le Bars, Didier; Billard, Thierry
Abstract: A broad spectrum of carbonyl substrates can be successfully transformed with agent (II).